Water quality and fluorescent dissolved organic matter dynamics of Dhaleshwari River - Mohinuzzaman, Mohammad; Mowa, Jannatul; Kabir, Mohammad Mahbub; Chowdhury, Muhammed Alamgir Zaman; Nesha, Meherun; Mostofa, Khan M. G.; Niloy, Nahin Mostofa; Shammi, Mashura; Tareq, Shafi M. (Frontiers in Water, 2025)
This study aimed to evaluate the physicochemical properties and the characteristics of the fluorescent dissolved organic matter (FDOM) in the Dhaleshwari River, located in the peripheral Dhaka district, Bangladesh. The Dhaleshwari River was selected as the study area due to the presence of a tannery industrial estate and various industries discharging effluents in the surrounding areas. The socioeconomic and ecological significance of the river is highly critical to the locality. Water samples were collected in the dry season for pH, electrical conductivity (EC), salinity, total dissolved solids (TDS), dissolved oxygen (DO), biochemical oxygen demand (BOD), chemical oxygen demand (COD), and FDOM analyses. The river water quality values were compared to the recommended standards of the Environmental Conservation Rules (ECR), and it was observed that the BOD and COD levels exceeded the limits. The water quality index (WQI) values showed that river water is extremely polluted, and the values significantly increased from the upstream to the Keraniganj BSCIC area. 3DEEM-PARAFAC analysis confirmed the presence of protein-like substances, terrestrial humic and fulvic acids, and degraded fulvic acids in the samples, which provided evidence of organic matter pollution. Relatively higher FDOM levels were found in the upstream area of the river compared to the downstream part. Furthermore, we found that with the increase in the river depth, the FDOM substances decreased due to the absorption of sunlight, microbial degradation, and photosynthesis. It is recommended that industrial estates implement proper wastewater treatment plants, and the Department of Environment (DoE) should take political and legislative actions to establish an adequate water quality monitoring system.